Tingkat Kemampuan Keterampilan Senam Lantai Siswa Kelas X MA Nihayatul Amal - Priandini, Dini; Milla Cahaya, Astried; Alamsyah, Firman (Jurnal Literasi Olahraga, 2022)
The aim of this research is to determine the skills of Class X MA Aliyah Nihayatul Amal Purwasari students' skills in learning floor exercise. The method used in this research is a survey method. Survey research is a quantitative research method used to obtain data that occurred in the past. data collection techniques using observation and research results tend to be generalized. This research was carried out by collecting data from students in Class X MA Aliyah Nihayatul Amal Purwasari in the Floor Gymnastics subject in physical education, sports and health. The action that the author took was to take data to see the skill level of class X students, MA Aliyah Nihayatul Amal Purwasari